Pembaharuan hukum Islam dan pemikiran gender di Indonesia: Munawir Sjadzali, Husein Muhammad, Nasaruddin Umar, dan Siti Musdah Mulia - Maulidina, Annaafi (Maliki Interdisciplinary Journal, 2024)
Islamic legal reform and gender thinking in Indonesia have been a major focus of academic and social discussion in recent decades. Figures such as Munawir Sjadzali, Hussein Muhammad, Nasaruddin Umar, and Siti Musdah Mulia have played key roles in formulating new views on Islamic law and gender issues. This article presents thoughts on their respective contributions in shaping a more inclusive discourse of Islamic law reform and more progressive thinking on gender in the Indonesian context. Through their diverse and innovative approaches, they have enriched the discussion on how Islam can adapt to changing times and respond to demands for gender equality. An exploration of their thoughts provides a clear picture of the complexities and dynamics in the process of Islamic law reform and gender thinking in Indonesia.